2021
DOI: 10.32507/attadib.v5i1.848
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Blended Learning Berbantuan Media Benda Konkret Untuk Meningkatkan Hasil Belajar Pada Materi Bangun Ruang Siswa Kelas 2 Sd Muhammadiyah 4 Surabaya

Abstract: Penerapan model bleanded learning dipadukan dengan media benda konkret dapat memaksimalkan  pembelajaran dan hasil belajar pada materi bangun ruang untuk siswa kelas 2 SD. Penelitian ini bertujuan mendeskripsikan penerapan model bleanded learning berbantuan  media benda konkret dan peningkatkan hasil belajar siswa kelas 2 SD Muhammadiyah 4 Surabaya dalam penerapan blended learning dengan berbantuan media kongkrit pada materi bangun ruang. Penelitian ini adalah penelitian tindakan kelas (PTK). Hasil penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…From this research, it can be concluded that the application of blended learning assisted by concrete object media through Zoom Meetings can improve student learning outcomes in geometry materials. Seen in student learning outcomes have increased from 54% before the research was conducted to 71% in the first cycle and to 89% in the second cycle of research [10].…”
Section: Resultsmentioning
confidence: 99%
“…From this research, it can be concluded that the application of blended learning assisted by concrete object media through Zoom Meetings can improve student learning outcomes in geometry materials. Seen in student learning outcomes have increased from 54% before the research was conducted to 71% in the first cycle and to 89% in the second cycle of research [10].…”
Section: Resultsmentioning
confidence: 99%
“…Dari hasil penelitian yang dilakukan (Islami et al, 2021) bahwasanya model pembelajaran bleanded learning pada dasarnya adalahgabungan pembelajaran tatap muka dengan virtual, dan halini dapat meningkatkan hasil belajar siswa di sekolah. Selain itu model pembelajaran bleanded learning dapat menumbuhkan kemamuan dalam berpikir kritis dalam diri siswa (Wihartini, 2019) The provision of classical guidance activities using a blended learning model is intended to provide insight and understanding to students so that they can use the information to plan their lives in the present and the future.…”
Section: Discussionunclassified
“…The research instrument that will be used is a test question sheet in the form of 10 multiple-choice questions. (Islami et al, 2021) 2. Observation, which aims to observe student activities during learning.…”
Section: Application Of Interactive Learning Media Mathematics Assist...mentioning
confidence: 99%